A review on the technological development of wind energy for power generation in the Philippines. - Magtoles, Lyca Marie (2023.)
Wind energy is a readily available, clean, and sustainable source of energy. It has become more competitive and has the potential to contribute significantly to renewable energy utilization in the future. In the Philippines, only a small portion of the total energy supply for power generation comes from wind energy. Additionally, only a few publications have been produced in the Philippines and the country still has so much more to do to maximize its full wind resource potential. This study discusses the current wind turbine technology available worldwide to convert wind energy into electrical energy and its applicability in the Philippine setting. The technologies discussed are horizontal axis wind turbine (HAWT), vertical axis wind turbine (VAWT), bladeless wind turbine (BWT), and offshore wind turbine (OWT). Based on this comprehensive review, the modern HAWT is still widely used in utility-based applications because of its high efficiency and mature technology. The Philippines has also been focusing on developing OWT and this has the potential to significantly increase the contribution of wind energy and renewable energy to the energy supply in the country. These two wind turbine technologies have high capacities and high efficiency at high wind speeds. Meanwhile, the VAWT and BWT can be used in areas with low and turbulent wind speeds, however, the current state of their technology is still not applicable for scalability. The mechanisms, design, advantages, and disadvantages of the four technologies, as well as the challenges and opportunities of the wind energy industry, are also discussed in this review.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Wind energy -- Philippines